1987
DOI: 10.1159/000184387
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Pathology in Chronic Dialysis Patients – an Autopsy Study of 78 Cases

Abstract: Autopsy data from 78 patients with end-stage renal disease (ESRD) treated with long-term hemodialysis were examined. Various pancreatic abnormalities were found in 47 (60%) patients. The most prevalent abnormality was pancreatitis which was seen in 22 patients (28%). Other lesions found with considerable frequency included fibrosis, hemosiderin deposits, calcification, cystic changes, amyloidosis and abscess formation. In addition hyalinization, atrophy or absence of islands of Langerhans and necrosis of perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 5 publications
4
102
0
2
Order By: Relevance
“…2), confirming previous findings in CKD rats [5] and ESRD patients [4]. Colon wall inflammation was significantly reduced in the dh404-treated CKD rats.…”
Section: Histological Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…2), confirming previous findings in CKD rats [5] and ESRD patients [4]. Colon wall inflammation was significantly reduced in the dh404-treated CKD rats.…”
Section: Histological Findingssupporting
confidence: 88%
“…Almost 30 years ago, Vaziri et al [4] showed the presence of inflammation throughout the gastrointestinal tract (including gastritis, enteritis, and colitis) in a postmortem analysis of 78 hemodialysis patients. Recent studies by our group have demonstrated disruption of the epithelial tight junction throughout the gastrointestinal tract and its association with endotoxemia, local and systemic inflammation, and oxidative stress in animal models of CKD [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of urea in intracellular and extracellular compartments, due to reduced renal function, generates high influx of this compound into the gastrointestinal tract where microbial ureases catalyze the hydrolysis of urea and generate large amounts of ammonia. Ammonium hydroxide, a by-product of ammonia, increases the intestinal pH, which leads to mucosal irritation and interferes with the growth of commensal bacteria, favoring the establishment of intestinal dysbiosis [78,79]. The negative impact of urea conversion by microbial urease over intestinal epithelial cells was demonstrated in an in vitro study when colonocytes were incubated with urea plus urease.…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%
“…Although the underlying mechanism for the relationship between ESRD dialysis and NODM are not fully understood, the factors associated with ESRD dialysis, including being older 2 , having histological abnormalities and dysfunction in the pancreas [4][5][6] , having CVD 2 , including stroke and heart failure, and in a state of chronic inflammation 7 , can induce insulin resistance and the development of type 2 DM.…”
Section: Risk Factors and Possible Mechanismsmentioning
confidence: 99%
“…ESRD patients on dialysis are always older and have multiple comorbidities, including cardiovascular disease (CVD), stroke and heart failure 2 . In addition, many of them have histological abnormalities and dysfunction of the pancreas [4][5][6] . They have also been found to be in a state of chronic inflammation associated with the development of insulin resistance and DM 7 .…”
Section: Introductionmentioning
confidence: 99%